Effects of perioperative cognitive function training on postoperative cognitive dysfunction and postoperative delirium: a systematic review and meta-analysis - Zhao, Li; Zhu, Hongyu; Mao, Wei; Zhou, Xuelei; Xie, Ying; Li, Linji (Frontiers in Neurology, 2023)
Background Randomized controlled trials (RCTs) have shown conflicting results regarding the effects of perioperative cognitive training (CT) on the incidence of postoperative cognitive dysfunction (POCD) and postoperative delirium (POD). We, therefore, performed a meta-analysis to assess the overall effects of studies on this topic. Methods We searched PubMed, Embase, the Cochrane Library, and Web of Science for all RCTs and cohort studies that investigated the effects of perioperative CT on the incidence of POCD and POD. Data extraction and quality assessment were conducted independently by two researchers. Results This study included nine clinical trials with a total of 975 patients. The results showed that perioperative CT significantly reduced the incidence of POCD compared with the control group [risk ratio (RR) = 0.5, 95% CI (confidence interval): 0.28–0.89, P = 0.02]. Nevertheless, for the incidence of POD, the difference between the two groups was not statistically significant (RR = 0.64; 95% CI: 0.29–1.43, P = 0.28). In addition, the CT group had less postoperative decline in the cognitive function scores compared with the control group [mean differences (MD): 1.58, 95% CI: 0.57–2.59, P = 0.002]. In addition, there were no statistically differences in length of hospital stay between the two groups (MD: −0.18, 95% CI: −0.93–0.57, P = 0.64). Regarding CT adherence, the proportion of patients in the cognitive training group who completed the planned duration of CT was 10% (95% CI: 0.05–0.14, P = 0.258). Conclusion Our meta-analysis revealed that perioperative cognitive training is possibly an effective measure to reduce the incidence of POCD, but not for the incidence of POD. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022371306, identifier: CRD42022371306.